2004
DOI: 10.1002/cphc.200301222
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electron Dynamics in Metals

Abstract: During the last decade, significant progress has been achieved in the rapidly growing field of the dynamics of hot carriers in metals. Here we present an overview of the recent achievements in the theoretical understanding of electron dynamics in metals, and focus on the theoretical description of the inelastic lifetime of excited hot electrons. We outline theoretical formulations of the hot-electron lifetime that is originated in the inelastic scattering of the excited quasiparticle with occupied states below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…In the Green functions method, the effect of interactions on the single-(quasi)particle properties are completely contained in the self-energy R. Most calculations of this quantity have been performed within the Hedin GW approximation [42,71] by taking the band structure of the material into account [19,51,72] instead of considering plane wave states as in the case of the homogeneous electron gas. In the many-body perturbation theory, the imaginary part of the self-energy R is expanded in terms of the single particle Green function G and the screened Coulomb interaction W(r, r 0 , x).…”
Section: Green Functions Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Green functions method, the effect of interactions on the single-(quasi)particle properties are completely contained in the self-energy R. Most calculations of this quantity have been performed within the Hedin GW approximation [42,71] by taking the band structure of the material into account [19,51,72] instead of considering plane wave states as in the case of the homogeneous electron gas. In the many-body perturbation theory, the imaginary part of the self-energy R is expanded in terms of the single particle Green function G and the screened Coulomb interaction W(r, r 0 , x).…”
Section: Green Functions Methodsmentioning
confidence: 99%
“…There are also a number of reviews on different theoretical approaches to this problem, see e.g. [18][19][20][21]. A very general review on current developments within this field can furthermore be found in [22].…”
Section: Introductionmentioning
confidence: 99%
“…A number of theoretical methods have also been developed for the evaluation of lifetimes, such as semiempirical methods based on the scattering theory 10,14-16 and firstprinciple approaches 17 based on the self-energy formalism of many-body perturbation theory ͑MBPT͒. 18 First-principle evaluations of lifetimes have been performed for a variety of metallic systems including simple metals, [19][20][21][22][23] noble, 19,20,[22][23][24][25][26] and transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, despite the important role of the hole-phonon relaxation, the available data on the timing of these processes are scanty and insufficiently accurate. The number of theoretical works on this subject is limited and incomparable to the numerous studies of relaxation time in metals [17][18][19]. The formerly developed methods and computer codes for the solid state theory [20] facilitate firstprinciple calculations for the temporal characteristics of the relaxation processes.…”
Section: Introductionmentioning
confidence: 99%